The Preference Level of Tempeh Snack Bar and Purple Sweet Potato Flour with Addition of Raisins - Hayyin, Syarah (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Chronic Energy Deficiency (CED) is a persistent lack of energy and protein in women of childbearing age (WCA) leading to health disorders. Preparations for WCA during the pre-conception period is very important to deal with pregnancy. The study aims to find out the preferred level of tempe bar snack and purple yam flour with raisins as a snack from CED and snack bar nutritional value with the best formula. This study is experimental and uses factorial design with 2 factors: tempeh proportion with purple yam flour (80%:20%, 60%:40% :40%) and raising of raisins (20%:40%). Tke results of the statistical analysis showed that the formulation affects the color, texture, and snack bars. The best snack bar contains 255.11 kg of energy, 39.9 g of carbohydrate, 10.8 g of protein, 8.04 g of fat, 3.53 g of fat, 3.53 mg of iron, 17.8 mg of vitamin C, and 7.34 g of fiber. This snack bar has been compatible with the quality requirement that contains at least 5% protein (16.9%).